THE STUDY GUIDE: BRIDGING THE GAP BETWEEN THE ACADEMIC AND - Vergie, Malvin (South African Journal of Higher Education, 2016)
This article is a critical reflection on the role of the study guide in bridging the gap between the academic culture represented by lecturers and the non-academic culture represented by students at an open distance learning (ODL) institution. The study guide has to facilitate the student in the world of a new and sometimes intimidating culture, namely the (tertiary) academic culture. When lecturers write for students, they must have an understanding of the challenges facing ODL students and write in clear, accessible language.